The effect of prolonged decalcification on the immunohistochemical staining of Leishmania infantum amastigotes in formalin-fixed, paraffin-embedded canine soft tissues (lymph nodes) - PAPADOGIANNAKIS, E; KOUTINAS, A; KONTOS, V (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this report was to present the preliminary results of the effect of prolonged decalcification on the immunohistochemical staining of Leishmania infantum in formalin-fixed, paraffin-embedded canine soft tissues. A heavily parasitized by Leishmania infantum amastigotes popliteal lymph node was used in this study. One half of a surgically excised lymphnode was processed according to a decalcification protocol (for 40 days), while the other half was processed without decalcification. Immunohistochemical staining for Leishmania infantum was then applied on both decalcified and non-decalcified lymph node sections. The amastigotes were stained and detected in non-decalcified sections, whereas a significant reduction of immunostaining was observed in decalcified sections. It is likely that parasite antigens are altered by the decalcification procedure, probably as a result of the long lasting effect of decalcifying acids on both the amastigotes and the host cell cytoplasm. Consequently, it seems that immunohistochemical detection of Leishmania infantum amastigotes is significantly affected following prolonged tissue decalcification.